Nefrolitíase e risco cardiovascular : avaliação da aterosclerose nos pacientes litiásicos - Freitas, Augustus Cesar Pinto de [UNIFESP] (2017)
Nephrolithiasis is considered a multifactorial disease, which prevalence has been increasing in the world. Many studies have been established a link between nephrolithiasis and systemic disease, including cardiovascular disease (CVD), metabolic syndrome (MS) and atherosclerosis. The main theories about the pathogenesis of early calculi’s matrix describe it like a biomineralization pathological and inflammatory process, with involvement of reactive oxygen species (ROS). Thereby, the calculi’s formation shares pathophysiological mechanisms suchlike that involved with another systemic disorders, which have high mortality and begins with atherosclerosis. Studies have shown the presence of ROS and your products in atherosclerosis, like oxidized low-density lipoprotein (LDLox), which is considered a marker of that disease. High levels of LDLox correlate significantly with CVD, including coronary and femoral artery disease. The antibody of LDLox (Ac Anti-LDLox) correlates less clearly with atherosclerosis. However, despite both, nephrolithiasis and atherosclerosis, exhibit pathophysiological mechanisms related to oxidative stress, we have not studies about LDLox in nephrolithiasis’ patients. This study aims to evaluate the serum levels of LDLox, antibory LDLox and others atherosclerosis markers in nephrolithiasis’ patients, according to the severity of the disease. It’s an translational cross-sectional study conducted between October 2015 and February 2017, involving 94 lithiasic patients, asymptomatic from the cardiovascular point of view, between 30-70 years old, watched in renal calculi clinic of Instituto de Medicina Integral Professor Fernando Figueira (IMIP) and 21 healthy controls. They were excluded when any anatomical abnormalities, chronic renal disease or cardiovascular disease were found or if they use statins. Pregnant women were also excluded. There were realized 24 hour urine measurements, serum measurements of atherosclerosis markers, like enzyme immunoassay to LDLox (Human Oxidized Low Density Lipoprotein (OxLDL) ELISA Kit; Elabscience Biotechnology Co., Wuhan, China) and Ac Anti-LDLox (OLAB IgG - Antioxidized LDL autoantibodies - ELISA Kit; Biomedica Medizinprodukte GmbH, Viena, Austria), following the manufacturer’s instructions. This study was approved by the Ethics Committee on Human Research of IMIP. Patients with nephrolithiasis were divided into group 1 (≥ 3 kidney stones) and group 2 (1-2 kidney stones). Both showed significantly higher LDLox levels (group 1: p= 0,02; group 2: 0,003) and higher LDLox/HDL (group 1: p=0,005; group 2: p=0,004) than controls. Patients in group 1 evidenced lower levels of Ac Anti-LDLox (p= 0,03) in relation to the control group. C-reactive protein were higher in patients with more severe disease (group 1; p=0,02). Our findings suggest that patients with renal stone disease have higher levels of LDLox, LDLox/HDL and PCR than healthy individuals. These findings indicate that this may be the link between nephrolithiasis, atherosclerosis and cardiovascular disease, more prevalent in patients with calculi.